(untitled) (Sustainability in Debate, 2023)
The paper aims to analyse the street-level bureaucrats’ (SLBs) perception of President Bolsonaro’s administration’s effects on Brazilian environmental policy, emphasising deforestation prevention and control in the Legal Amazon1. Besides the policy dismantling concepts, a theoretical model integrating three complementary analytical dimensions of SLBs’ action – institutional, individual, and relational – was employed in a case-oriented investigation of environmental bureaucrats – Ibama Inspectors and ICMBio Agents. The inquiry used Systematic Content Analysis on interviews with these agents involved in deforestation inspection and control activities. The empirical results confirm the hypotheses that an active dismantling process has been ongoing since the beginning of Bolsonaro’s administration; however, the perceptions of Ibama inspectors seem more intense, especially regarding the institutional dimension. The research illustrates the adverse effects of this process on the agencies and bureaucratic capacities, generating paralysis and setbacks in deforestation inspection and control policies and posing serious risks to the environmental protection in the country. This article contributes to the advancement of knowledge about the strategies that a far-right populist government deliberately adopted to reduce the role of the State, weaken professional bureaucracy, dismantle policies and favour particular interests of groups.